2022
DOI: 10.1002/jcc.26879
|View full text |Cite
|
Sign up to set email alerts
|

The physical nature of the ultrashort spike–ring interaction in iron maiden molecules

Abstract: The so-called 'iron maiden' molecules belong to one of the most interesting subgroups of cyclophanes due to the presence of the ultrashort interaction between the C X apical bond and the benzene ring. This article presents an in-depth theoretical study of 16 'iron maiden' molecules, in which X = H, F, Cl or Br and the side chains are of various lengths and types: CSC, CSCC, CCC, and CCCC. It is shown that the H ! F ! Cl ! Br substitution leads to a significant expansion of the 'iron maiden' molecule. Shorter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…This is another argument that the Ng• • • π interactions in endohedral complexes are destabilizing [18]. It is worth adding here that negative MBO values have also been found more recently for some cation• • • C interactions in endohedral cation@superphane complexes [19] and for X• • • π (X = H, F, Cl) interactions in in forms of some "iron maiden" systems [20].…”
Section: Mayer Bond Ordersupporting
confidence: 51%
See 2 more Smart Citations
“…This is another argument that the Ng• • • π interactions in endohedral complexes are destabilizing [18]. It is worth adding here that negative MBO values have also been found more recently for some cation• • • C interactions in endohedral cation@superphane complexes [19] and for X• • • π (X = H, F, Cl) interactions in in forms of some "iron maiden" systems [20].…”
Section: Mayer Bond Ordersupporting
confidence: 51%
“…The results of the studies presented here can be confronted with the numerous bond paths that appear between the guest atoms and the host atoms (e.g., Ng• • • C) in diverse endohedral complexes [13,14]. It is therefore clear that these bond paths should be regarded as counterintuitive [15][16][17][18][19][20] and that their presence is not at all, as many still believe, evidence of interatomic stabilization.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…−2.8 kcal/mol. Apart from the aforementioned accompanying hydrogen bonds, the molecular graphs of dimers IDipp HF and IDipp HCN also show the presence of numerous C-H⋯H-C interactions, which, however, seems to be a fairly common feature in the case of crowded systems with many C-H bonds [ 80 , 125 , 126 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…Positive values of λ 2 indicate steric repulsion and negative values reflects attractive forces. [90][91] It can be observed that all interactions shows negative λ 2 values which implies that the nature of interactions within the BCPs are regarded as 1 stabilizing interactions due to the superiority of attractive forces.…”
Section: Tittlementioning
confidence: 99%